Studi Eksploratif Alkalisasi NaOH pada Proses Degumming Serat Daun Nanas terhadap Pengurangan Massa dan Kekuatan Tarik: Indonesia - Budiman, Ahmad Satria; Septiadini, Asyifa; Hadna, Aulia Muchammad Roqieba (Asian Journal of Innovation and Entrepreneurship, 2026)
Pineapple leaf fiber is a natural fiber that remains underutilized despite its potential. This fiber is composed of bundles bound by pectin, hemicellulose, and lignin, which must be removed through a degumming process. This study aims to investigate the effects of NaOH concentration and processing temperature variations on the characteristics of pineapple leaf fibers, including mass reduction, tensile strength, and elongation. The experimental method involved alkali treatment using NaOH solutions with concentrations of 1%, 3%, 5%, 7%, and 10%, at three temperature variations of 60°C, 80°C, and 100°C. Each sample was weighed to determine mass reduction, followed by tensile strength and elongation testing. The experimental data were analyzed using R-statistics to evaluate the significance of differences among treatments. The results showed that higher NaOH concentrations and temperatures lead to greater mass reduction, with the highest value of 31.92% obtained at 100°C and 10% NaOH. However, this condition also caused a decrease in tensile strength to below 10 cN/tex and an increase in elongation to more than 6%. Statistical analysis revealed that differences in treatments were not significant at 60oC (p > 0,9), but become significant at 80-100oC (p < 0,05). The study concludes that insufficiently strong treatments are ineffective, while excessively strong treatments may cause cellulose degradation, leading to decreased mechanical properties of the fibers.